2016
DOI: 10.18520/cs/v110/i12/2261-2267
|View full text |Cite
|
Sign up to set email alerts
|

Autodetection in <i>Helicoverpa armigera</i> (Hubner)

Abstract: Autodetection is an olfactory behavioural process where the females of some species respond to their own pheromonal blends. Through electroantennogram studies it has been proved that the gravid females of Helicoverpa armigera (Hubner) respond to their pheromone blend consisting of Z-11-hexadecenal and Z-9-hexadecenal in the ratio 97 : 3. Male antennae respond more strongly than virgin female antennae. However, antennae of gravid females elicit strong response than unmated males. Also, males showed strong respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Bakthavatsalam and coworkers [ 134 ] also proved that gravid females of H. armigera (Hubner) respond to their pheromone blend (mixture of ( Z )-11-hexadecenal and ( Z )-9-hexadecenal in 97:3 ratio) eliciting stronger responses than unmated males. However, virgin or gravid females showed poor response in wind-tunnel studies, and an oviposition bioassay where gravid females were allowed to oviposit in the presence and absence of pheromone odors indicated that there was no difference in the number of eggs laid.…”
Section: Sex Pheromone Autodetectionmentioning
confidence: 99%
“…Bakthavatsalam and coworkers [ 134 ] also proved that gravid females of H. armigera (Hubner) respond to their pheromone blend (mixture of ( Z )-11-hexadecenal and ( Z )-9-hexadecenal in 97:3 ratio) eliciting stronger responses than unmated males. However, virgin or gravid females showed poor response in wind-tunnel studies, and an oviposition bioassay where gravid females were allowed to oviposit in the presence and absence of pheromone odors indicated that there was no difference in the number of eggs laid.…”
Section: Sex Pheromone Autodetectionmentioning
confidence: 99%
“…Early studies on Bombyx mori and other moth species have led to the notion that females are generally anosmic for their own pheromone (Schneider, ). However, over the last decades numerous electrophysiological and behavioral studies have shown for a variety of lepidoteran species (reviewed in Holdcraft et al ., ) that female moths have the ability to recognize components of the pheromone they release; this phenomenon was designated as “autodetection” (Ochieng et al ., ; Schneider et al ., ; Bakthavatsalam et al ., ). This term could suggest self‐detection of compounds released by the pheromone‐producing individual, however, all the reported cases describe a detection of pheromones released by conspecific females (Holdcraft et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…2,[4][5] These explanations, however, do not consider how the other portion of the insect populationfemale insectsmay respond to unnaturally large doses of synthetic pheromones. Despite increasing evidence that females are able to 'autodetect' and alter their reproductive behavior in response to their own pheromones, [7][8][9][10][11][12][13] far fewer studies have explored mating disruption effects on female insects. In particular, there is a dearth of information on autodetection in nonlepidopteran species and whether female behavior contributes to or hinders mating disruption success.…”
Section: Introductionmentioning
confidence: 99%